The lung cancer management guidelines - Jazieh Abdul-Rahman (Annals of Thoracic Medicine, 2008)
The Lung Cancer Guidelines Committee developed 2008 Lung Cancer Management Guidelines based on available evidences in the literature. These guidelines are stage-dependent and addressing the most common clinical scenarios. They address diagnosis, work-up, treatment, and follow up of lung cancer.